Menggali Potensi Dalam Proses Pembelajaran Strategi Afektif untuk Meningkatkan Keterlibatan Siswa dan Kualitas Pembelajaran - Gusmaneli Gusmaneli; Anggi Ladiva Junaidi; Nada Ranjani (CV. Aksara Global, 2024)
This research discusses the potential in the learning process of affective strategies as an effort to improve student engagement and learning quality. The affective strategy approach emphasizes the development of students' social and emotional skills, as well as strengthening positive relationships between teachers and students. The research method involves analyzing the literature to understand the concept of affective strategies in the context of learning. Findings show that the implementation of affective strategies can result in improvements in learning motivation, social interaction, and academic achievement. However, challenges related to the integration of affective strategies in the curriculum and classroom management were also identified. Implications of this study include the importance of teacher training in the implementation of affective strategies, as well as the active role of students in utilizing the learning potential presented by this approach.